Natural Course of Early Detected Acute Peripancreatic Fluid Collection in Moderately Severe or Severe Acute Pancreatitis - Dong Wook Lee; Ho Gak Kim; Chang Min Cho; Min Kyu Jung; Jun Heo; Kwang Bum Cho; Sung Bum Kim; Kook Hyun Kim; Tae Nyeun Kim; Jimin Han; Hyunsoo Kim (Medicina, 2022)
Background and Objectives: Acute peripancreatic fluid collection (APFC) is an acute local complication of acute pancreatitis (AP) according to the revised Atlanta classification. Sometimes APFC resolves completely, sometimes it changes into a pseudocyst or walled-off necrosis (WON), so called late complications. The aim of this study is to investigate the natural course of APFC detected on early computed tomography (CT) in moderately severe (MSAP) or severe AP (SAP). Materials and Methods: From October 2014 to September 2015, patients with MSAP or SAP were enrolled if there was APFC within 48 h of onset on imaging studies at six medical centers. The status of fluid collection was followed 4–8 weeks after onset. Initial laboratory findings, CT findings and clinical scoring systems were analyzed. Results: A total of 68 patients were enrolled and APFC was completely resolved in 32 (66.7%) patients in the MSAP group and 9 (34.6%) in the SAP group. Patients with a high bedside index for severity in acute pancreatitis (BISAP) score (≥3 points) were common in the SAP group. C-reactive protein (CRP) after 48 h from admission and BUN level were also high in the SAP group. In multivariate analysis, BISAP score (≥3 points), elevation of CRP after 48 h (≥150 mg/L) and nasojejunal feeding after 48 h were risk factors for the development of late complications. Conclusions: Spontaneous resolution of APFC was more common in MSAP group and APFC can be changed to pseudocyst or WON in patients with elevated BISAP score, CRP level after 48 h, and non-improved abdominal pain.